Pengembangan Web Service Sistem Informasi Sekolah - Sa’diyah, Za’imatus; Aziz, Kevin Elmy; Dardiri, Muhammad Hudan; Yaqin, M. Ainul (STIKOM Tunas Bangsa Pematangsiantar, 2020)
School information system is a system that provides information to support the operational, management, and decision making functions of an organization. Information sources within the information system that support day-to-day management operations such as transaction processing, status clarification, and so forth. School information systems generally consist of a variety of systems, including academic, financial, library and staffing systems. With a variety of systems in a school information system, it is necessary to integrate between systems aimed at avoiding data duplication in each system and increase system flexibility which can be achieved by utilizing web service technology. The purpose of this research is to design a web service on information systems schools that comply with the National Education Standards (SNP) use the REST web service architecture. The results of the development of an information system web service design that is by mapping class diagrams that will be made in the design of school web services by adding modules to JIBAS with the Minister of National Education Regulation in accordance with 8 BSNP standards.